Comparison of Situational Coping Strategies, Psychological Well-Being and Life Satisfaction in Athletic and Normal Students - Masoumeh Ahmadi; Mehrdad Hasanzadeh; Shiva Yousefzadeh Ghara Aghaji; Leila Kaabi Amir (Research in Sport Management and Marketing)
Purpose: Physical activity includes a wide range of health benefits that can protect people from diseases and provide and strengthen their mental and physical health. Therefore, in the present study, situational coping strategies, psychological well-being and life satisfaction in athletic and normal students will be compared.Method: The leading research method was descriptive causal-comparative. The statistical population of this study was all undergraduate students of Mohaghegh Ardabili University. From this population, by sampling multi-stage clusters (university, faculty, department and finally the classroom, respectively), 200 people were selected. (100 athletes and 100 normal people) and the Situational Coping Strategies Questionnaire (SCSBQ-28), the Ryff Psychological Well-Being Scale (RSPWB-18) and the One-Question Life Satisfaction Scale (LSS-1) were administered to them. The method of analysis was multivariate analysis of variance (MANOVA).Results: The results showed that athletes use uncompromising strategies significantly less than normal people (MD= -1.478, P= 0.023). Also, psychological well-being (MD= 7.667, P< 0.001) and life satisfaction (MD= 0.956, P= 0.007) of athletes are significantly higher and with a very desirable level than normal people.Conclusion: Cultural and sports managers can encourage individuals and organizations to perform and budget to increase these activities by considering the psychological benefits of sports activities. Psychotherapists and counselors should also consider sports activities as behavioral techniques to promote well-being and satisfaction.